The Voice of Objects in The Old Curiosity Shop - Hollington, Michael (Australasian Journal of Victorian Studies, 2009)
Curiosities are objects on sale in an antique dealer’s - bric à brac, knick-knacks, souvenirs, mementos. So The Old Curiosity Shop is about what we can think of as commodities, objects on display and for sale. A fine new book by Catherine Waters, Commodity Culture in Household Words, offers plenty of material for a new focus on objects in Dickens which reinvigorates past, and some of it rather crude, Marxist criticism of Dickens’s works. Its focus is Dickens’s journalism, and that of the staff of the magazine he edited between 1850 and 1859, but its arguments can be used, as I do here, to provide an insight into the fiction. Even if the discussion of Dickens’s novel takes precedence here, and the consideration of its possible critical and theoretical underpinning is brief and largely confined to the end of the essay, my approach here is in fact an attempt to combine Waters’s work, both with an important but still little known essay on The Old Curiosity by the significant German philosopher and critic Theodor Adorno, and with some aspects of recent work by Bill Brown about what he calls ‘thing theory’.